Factorial analysis and invariance by sex and age of the Anger Rumination Scale ARS Spanish version - Toro, Ronald; García-García, Juan; Zaldívar-Basurto, Flor (Anales de Psicología / Annals of Psychology, 2020)
Anger rumination is perseverative thinking about a personally significant event that occurred to the person or others that leads to anger and constitutes a risk factor for aggression. The aim was to perform a confirmatory factor analysis and invariance by sex and age of the Anger Rumination Scale [ARS]. A non-probabilistic sample of 640 people between 18 and 63 years old (M = 31.07, SD = 11.27), grouped by sex (252 men, 378 women) and ages (278 under 25 years old, 352 over 25 years old) was formed. The instruments were the ARS and the RPQ reactive and proactive aggression questionnaire. It was found that the ARS presents a favorable fit in a four-factor model correlated with residual covariances. In turn, it was invariant between sexes and ages after imposing progressive restrictions on the confirmed model and presented significant correlations with reactive and proactive aggression as evidence of the validity of predictive criteria. It was concluded that the ARS presents adequate indicators of reliability and validity to be used in the Colombian context.